Proteomic Response of Pseudomonas aeruginosa PAO1 Adhering to Solid Surfaces - Guilbaud, Morgan; Bruzaud, Jérôme; Bouffartigues, Emeline; Orange, Nicole; Guillot, Alain; Aubert-Frambourg, Anne; Monnet, Véronique; Herry, Jean-Marie; Chevalier, Sylvie; Bellon-Fontaine, Marie-Noëlle (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a pathogenic micro-organism responsible for many hospital-acquired infections. It is able to adhere to solid surfaces and develop an immobilised community or so-called biofilm. Many studies have been focusing on the use of specific materials to prevent the formation of these biofilms, but the reactivity of the bacteria in contact to surfaces remains unknown. The aim of this study was to evaluate the impact of the abiotic surface on the physiology of adherent bacteria. Three different materials, stainless steel (SS), glass (G) and polystyrene (PS) that were relevant to industrial or medical environments were characterised at the physicochemical level in terms of their hydrophobicity and roughness. We showed that SS was moderately hydrophilic and rough, potentially containing crevices, G was hydrophilic and smooth while PS was hydrophobic and smooth. We further showed that P. aeruginosa cells were more likely able to adhere to SS and G rather than PS surfaces under our experimental conditions. The physiological response of P. aeruginosa when adhering to each of these materials was then evaluated by global proteomic analysis. The abundance of 70 proteins was shown to differ between the materials suggesting that their abundance was modified as a function of the material to which bacteria adhered. Our data lead to enabling the identification of abundance patterns that appeared to be specific to a given surface. Taken together, our data showed that P. aeruginosa is capable of sensing and responding to a surface probably via specific programmes to adapt its physiological response accordingly.